Tradhisi Prana Pratista di Desa Ngliman Kecamatan Sawahan Kabupaten Nganjuk "Tintingan Foklor" - Syawalna, Dhea Amanda; Susilo, Yohan (Jurnal Online Baradha, 2023)
ABSTRACT Prana Pratista tradition is a tradition that developed in Ngliman village, Sawahan District, Nganjuk Regency. This tradition is carried out by the entire ngliman community every year to purify themselves in order to welcome the month of Suro or the Islamic New Year and for ruwat Sedudo waterfall. Prana pratista tradition has a close relationship between humans and the surrounding environment, especially Sedudo waterfall, which is the main source in the village of Ngliman. The existence of one of the traditions in Ngliman village is an interesting thing to study. The purpose of this study is to explore the origins of the tradition, explain the equipment or medicine needed in the tradition and the meaning contained in the equipment or medicine. Describes the function of prana pratista tradition in Ngliman village in every aspect such as education, social, language style or satire, entertainers and in community criticism. As well as explaining how the efforts of the community to preserve in order to keep this tradition is not shifted era. This study uses the study of focal focal semi-oral, and this study uses qualitative descriptive method. The conclusion of this study is to present a result that shows the existence of this tradition and also describes that people are able to assess the function of this tradition. Keywords: Javanese culture, Folklore, and The Prana Pratista Tradition ABSTRAK Tradhisi Prana Pratista merupakan tradisi yang berkembang di desa Ngliman, Kecamatan Sawahan, Kabupaten Nganjuk. Tradisi yang dilakukan oleh seluruh masyarakat ngliman ini pada tiap tahunnya untuk mensucikan diri guna menyambut bulan Suro atau tahun baru islam serta untuk ruwat air terjun Sedudo. Tradisi Prana Pratista mempunyai hubungan erat antara manusia dan alam sekitarnya khususnya air terjun Sedudo, yang merupakan sumber utama di desa Ngliman. Eksitensi dari salah tradisi yang berada di desa Ngliman ini merupakan suatu hal yang menarik untuk diteliti. Tujuan penelitian ini guna mengupas tentang asal muasal adanya tradisi tersebut, menjelaskan perlengkapan atau ubarampe yang diperlukan dalam tradisi tersebut dan makna yang terkandung dalam perlengkapan atau ubarampe tersebut. Mendeskripsikan mengenai fungsi tradhisi Prana Pratista di desa Ngliman ini dalam setiap aspek seperti pendidikan, sosial, gaya bahasa atau sindiran, penghibur serta dalam kritik masyarakat. Serta menjelaskan mengenai bagaimana upaya para masyarakat untuk melestarikan guna menjaga agar tradisi ini tidak tergeser jaman. Penelitian ini menggunakan kajian foklor yakni foklor setengah lisan, serta penelitian ini menggunakan metode deskriptif kualitatif. Kesimpulan dari penelitian ini adalah menyajikan sebuah hasil yang menunjukan eksistensi tradisi ini dan juga menjabarkan bahwa masyarakat mampu menilai fungsi tradisi ini. Kata Kunci: Kebudayaan, Foklor, dan Tradisi Prana Pratista.